Increased anti- EBV VCA IgG antibody levels are associated with need for surgery in patients developing upper respiratory tract complications. (August 2018) - Arslan, Hande; Çandar, Tuba; Vural, Özge
Abstract: Introduction: The immune reaction developing against Ebstein-Barr virus (EBV) infection may be one of the major determinants of severe adenoid hypertrophy (AH) and chronic otitis media with effusion (COME) needing surgery. In this study, we aimed to investigate the relationship between these antibodies and the need for surgery due to complications such as severe AH and COME. Methods: Sixty consecutive patients <15 years old who were admitted to our outpatient clinics between January 2014 and December 2015 with severe AH ± COME and underwent adenoidectomy ± ventilation tube insertion and 129 control patients who had a history of EBV infection at least three months before the inclusion to the study without current symptoms of upper airway obstruction and middle ear disease were included in this study. Two groups of patients and a control group were studied: a) children who underwent adenoidectomy alone with no middle ear disease (group 1), b) children with COME and AH who underwent adenoidectomy and tympanostomy with ventilation tube insertion (group 2), and c) control group without adenoid hypertrophy or otitis media with effusion. Results: Patients who needed surgery (Group 1 and 2) had significantly higher levels of anti-EBV VCA IgG antibodies than control patients (19.8 ± 16.4 vs. 1.7 ± 0.8 S/CO, p < 0.001). Anti-EBV VCA IgM levels did not differ between groups. Group 2 patients had also higher levels of Anti-EBV VCA IgG antibodies than group 1 patients (35.8 ± 16.7 vs. 11.8 ± 8.5 S/CO, p < 0.001). ROC curve analysis resulted in a cut-off point of 2.92 S/CO level for anti-EBV VCA IgG antibodies for need for surgery in EBV infected patients with 97% sensitivity and 98% specificity. Conclusion: Markedly increased serum anti-EBV VCA IgG antibodies in children who developed upper respiratory tract complications such as severe AH and COME may show the significant role of enhanced immune system reaction in the pathogenesis of these complications due to EBV infection.